Improving photocatalytic activity of BioCl nanodiscs under visible light simulation through loading with silver nanoparticles - Chen, Shuang (2015)
Today, photocatalysts are not broadly tapped on in the wastewater treatment process because existing photocatalysts such as Titanium Dioxide (TiO2) still face noteworthy disadvantages. Foremostly, TiO2 is only capable of attaining high photocatalytic activity under Ultraviolet (UV) Light irradiation. Next, its speedy recombination of charges will impair photodegradation efficiency. As an alternative to TiO2, Bismuth Oxychloride (BiOCl) is proposed due to its special physical and chemical properties. Small amount of photocatalytic activity of BiOCl is observed under visible light simulation. Thus, alteration of BiOCl to improve its photocatalytic activity is pertinent. This report aims to increase BiOCl activity through doping with noble metal. Nanodisc BiOCl samples consisting of length of 150 to 250nm and thickness of 20-30nm were synthesised through hydrothermal method. BiOCl is generated under different temperature to form products named T120, T140, T160 and T180 respective to their time. The different temperatures do not show significant effect on BiOCl and the product of T120 is selected for noble metal deposition. Ag is doped on the surface of the BiOCl by Silver Nitrate (AgNO3) with photoreduction method under visible light irradiation. BiOCl and Ag-loaded BiOCl are characterised using XRD, FESEM, HRTEM, EDX, XPS and UV-Vis-Spectra. The photocatalytic activity of BiOCl and Ag-loaded BiOCl were evaluated by the visible light photodegradation of organic pollutants, Sulfanilamide (SNM). Ag-loaded BiOCl produced more positive results than pure BiOCl. This is proof that photocatalytic activity of BiOCl increase with doping of Ag.